MIYELOARHITEKTONICS OF KNEE JOINT CAPSULE OF CATS - Novak, V.P.; Bevz, O.S.; Melnichenko, A.P.; Nechiporuk, Ye.V. (World of Medicine and Biology, 2019)
The knee joint has a wide range of movements, and the proper neuroanatomical organization is critical for knee stability. The synovium of the joint performs a number of functions, which ensure the normal functioning of the joint under normal conditions, various loads and in the event of pathological changes in the local nature and the body as a whole. Distribution, location and spatial localization of mechanoreceptors are important for the shortness and accuracy of the neural signal in the proprioceptive information necessary to maintain functional stability.Damage to articular mechanoreceptors may lead to proprioceptive deficiencies that can lead to periodic instability.During the total arthroplasty, most of the articular capsule is removed, including most mechanoreceptors important for proprioception, which potentially limits postoperative functional recovery and has an elongated deficit of proprioception.Therefore the purpose of the present work was to study myeloarhitectonics and topography of nerve trunks, fibers, endings and to clarify which anatomical part of the capsule is less invasive.Despite the rather active study of the receptor apparatus of the capsule of the knee joint of cats, the question of statistical processing of the presence of nerve structures of surface-antagonists of capsules is not sufficiently investigated. The article presents the quantitative relations of the nerve elements of the articular capsule of cats in the anatomical parts-antagonists of the knee joint (lateral, medial, dorsal, planar). Nerve structures were shown by the neuromorphological method – the impregnation with silver nitrous oxide by the methods of Bilshovsky-Gros in the modifications of Lavrentiev and Campos, which we united. It has been statistically demonstrated that the dorsal part of the articular capsule is the least saturated nerve structure. Poor reflexogenic areas are located in the medial, lateral and dorsal parts of the capsule due to the smaller number of encapsulated endings. The receptors are represented by the corpuscules of Fater-Pacini, Rufini, Krause and free ones. In the capsule of the knee of cats, as representatives of phalanoid animals, the vast majority of encapsulated nerve endings than free ones. It is possible that the multiplicity and variability of the receptors, their localization and the nature of the formation of reflexogenic zones are associated with species-specific features, as well as the speed of movement and the type of support. These data may be used to clarify the patterns of pain sensation in the knee joint, to use the acupuncture and acupressure zones, minimize damages for access to the organo-complex of the synovial medium, and also in the comparative aspect for the evaluation of the experimental material.
Keywords: knee joint; capsule; reflexogenic zone; free receptors; encapsulated nerve endings